Controlling Regioselectivity in Palladium‐Catalyzed C−H Activation/Aryl–Aryl Coupling of 4‐Phenylamino[2.2]paracyclophane - Zippel, Christoph (Chemistry, 2020)
Selective activation/functionalization of C−H bonds has emerged as an atom‐ and step‐economical process at the forefront of modern synthetic chemistry. This work reports palladium‐catalyzed exclusively para‐selective C−H activation/aryl–aryl bond formation with a preference over N‐arylation under the Buchwald–Hartwig amination reaction of 4‐phenylamino[2.2]paracyclophane. This innovative synthetic strategy allows a facile preparation of [2.2]paracyclophane derivatives featuring disparate para‐substitutions at C‐4 and C‐7 positions in a highly selective manner, gives access to a series of potential candidates for [2.2]paracyclophane‐derived new planar chiral ligands. The unprecedented behavior in reactivity and preferential selectivity of C−C coupling over C−N bond formation via C−H activation is unique to the [2.2]paracyclophane scaffold compared to the non‐cyclophane analogue under the same reaction conditions. Selective C−H activation/aryl–aryl bond formation and sequential C−N coupling product formation is evidenced unambiguously by X‐ray crystallography.